A proposed Petri Nets Model for updating XML documents on a multicore architecture - Wadi, Alaa M.; Lee, Sai Peck (2009)
Updating XML documents is getting more and more attention from both academic and commercial fields. The time needed to update XML documents is a key factor for the success of any application especially for those related with the c-commerce. In this article, we suggest using Petri Nets as a tool for designing a concurrent model that is able to achieve XML update operations. Also, we suggest using the same tool for validating these operations. Finally, we propose to apply the concurrent model by using multithreading on a Multicore Architecture. We plan to prove that these models can minimize the time spent in updating and validating XML documents